On the accuracy of N-body simulations at very large scales - Rigopoulos, Gerasimos; Valkenburg, Wessel (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We examine the deviation of cold dark matter particle trajectories from the Newtonian result as the size of the region under study becomes comparable
In original form 2014 February 21
Gesehen am 18.06.2020